2022
DOI: 10.1007/s00192-022-05299-y
|View full text |Cite
|
Sign up to set email alerts
|

Total trans-obturator tape (TOT) removal; a case series including pain and urinary continence outcomes

Abstract: Introduction and hypothesis For many years, mid-urethral mesh tape (MUT) was the gold-standard procedure for management of stress urinary incontinence (SUI). However, significant concerns were raised over its safety. We present a case series of total trans-obturator tape (TOT) removals, performed in a tertiary unit over a 3-year period. We aim to evaluate improvement of pain and change in urinary continence symptoms following mesh explantation. Methods This is a retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…This was a surprising finding as the midurethral tape was an effective treatment option for stress incontinence. The rate of recurrent SUI is comparable to a similar smaller cohort 9 . A high rate of recurrent stress incontinence may also be partly explained by 20% of women who underwent tape revision before TETOT.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…This was a surprising finding as the midurethral tape was an effective treatment option for stress incontinence. The rate of recurrent SUI is comparable to a similar smaller cohort 9 . A high rate of recurrent stress incontinence may also be partly explained by 20% of women who underwent tape revision before TETOT.…”
Section: Discussionsupporting
confidence: 65%
“…High rates of loss to follow‐up (60%−70%) have been common in studies reporting outcomes after mesh excision 8,12 . A review of the literature revealed commonality between other studies—frequently, studies reporting outcomes of stress incontinence after mesh excision typically carry heterogenous groups of MUT routes, report outcomes over a short period of time, and are limited to vaginal excisions 8,9,20–23 . These rates cannot be generalized to those undergoing TETOT, in the long‐term.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations